Criteria for diagnosis and attribution of an occupational musculoskeletal disease - Violante, Francesco Saverio (La Medicina del Lavoro, 2020)
Background: Criteria for diagnosis and compensation of occupational musculoskeletal diseases varies widely between countries as demonstrated by the large differences between countries with comparable economics and social systems (for example, within the European Union). Several countries have a list of occupational diseases and sometimes these lists include diagnostic and attribution criteria, but these criteria are usually not very specific, and they may also be very different. Objectives: The aim of this paper is to explicitly define what are the information needed for an evidence-based diagnosis and attribution of an occupational musculoskeletal disease. Methods: Based on the general framework of evidence-based medicine, a review is presented of the information required to define: - when a musculoskeletal disease is present, according to the best available techniques; - how to define a relevant exposure to biomechanical risk factors, according to the best available techniques. Results: Criteria are presented to combine information regarding the diagnosis of a musculoskeletal disease and exposure to biomechanical risk factors for an evidence-based attribution of the disease to the occupational exposure. The criteria use a probabilistic model that combine epidemiologic and medical findings, workplace exposure assessment, and non-occupational factors evaluation. Discussion: The use of the proposed criteria may improve the process of diagnosis and attribution of an occupational musculoskeletal disease. In addition, it makes possible to associate a probability rank to the attribution and, ultimately, it may improve the overall quality of the decisional process of the occupational physician.